An information centric framework for creating virtual environments to support micro surgery - Cecil, J.; Pirela-Cruz, Miguel (International Journal of Virtual Reality, 2016)
In this paper we discuss the creation of an information centric framework to develop a virtual reality environment for micro surgery. An information model of micro surgery was built through interactions with an expert micro surgeon using the engineering Enterprise Modeling Language (eEML). The overall approach and architecture of the micro surgical environment is discussed. An enterprise level surgical manager, surgical planner and other components work together to enable the functioning of the virtual environment for micro surgery. Such virtual environments are essential to educating / training young budding surgeons..